1991
DOI: 10.1128/mcb.11.6.3217
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation by positive and negative translational regulators of GCN4.

Abstract: GCN4 is a transcriptional activator of amino acid biosynthetic genes in Saccharomyces cerevisiae whose expression is regulated by amino acid availability at the translational level. GCD1 and GCD2 are negative regulators required for the repression of GCN4 translation under nonstarvation conditions that is mediated by upstream open reading frames (uORFs) in the leader of GCN4 mRNA. GCD factors are thought to be antagonized by the positive regulators GCN1, GCN2, and GCN3 in amino acid-starved cells to allow for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 58 publications
7
108
0
Order By: Relevance
“…Possibilities for the role of these 5Ј untranslated regions include control over translocation of the mRNA within the cell, translational control, or transcriptional control. Although no upstream, in-frame translation start sites were seen, it is possible that short out-of-frame translation products could be used to regulate protein synthesis, as has been observed for yeast GCN4 (33,34). In addition, it has been observed that ORG mRNA is found both at the dendrite and at the axon (28).…”
Section: Discussionmentioning
confidence: 93%
“…Possibilities for the role of these 5Ј untranslated regions include control over translocation of the mRNA within the cell, translational control, or transcriptional control. Although no upstream, in-frame translation start sites were seen, it is possible that short out-of-frame translation products could be used to regulate protein synthesis, as has been observed for yeast GCN4 (33,34). In addition, it has been observed that ORG mRNA is found both at the dendrite and at the axon (28).…”
Section: Discussionmentioning
confidence: 93%
“…Addition of eIF-2 increased initiation on the upstream AUG. The conclusion was that the increased availability of active eIF-2 increased the concentration of eIF-2-Met-tRNA-GTP-40S complex and therefore increased initiation on the upstream AUG. A very similar mechanism regulates yeast GCN4 mRNA translation (Cigan et al, 1989(Cigan et al, , 1991. Initiation codon selection by eIF-2 has now been shown for capdependent initiation (Dasso et al, 1990; this study), for initiation by leaky scanning and termination-reinitiation (Cigan et al, 1988) and for internal initiation on FMDV-CAT RNA (Figs 3 6).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of eIF-2 the ribosome is unable to initiate at the nearby AUG and moves downstream to AUGL. o, a situation very similar to initiation on the yeast GCN4 mRNA (Cigan et al, 1989(Cigan et al, , 1991. During movement towards AUGLb, eIF-2 binds to 40S, unless the activity or amount of eIF-2 is too low, resulting in abortive initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown in yeast nitrogen base medium at 30ЊC to 5 ϫ 10 6 to 8 ϫ 10 6 cells per ml, washed twice with ice-cold H 2 O, resuspended in ice-cold lysis buffer consisting of 40 mM PIPES [piperazine-N,NЈ-bis(2-ethanesulfonic acid)] (pH 6.0)-100 mM NaCl-1 mM dithiothreitol containing protease inhibitors (11), and lysed by agitation with glass beads. The cell extract was resolved and immunoblotted as described previously (11) with anti-Prt1p primary antibody against Prt1p (11) or eIF-2␣ (a gift from Alan Hinnebusch).…”
Section: Construction Of Mutations In Vitromentioning
confidence: 99%